Case report: Total hip replacement using Innoplant system in a dog with chronic hip luxation and contralateral pelvic limb amputation - McCartney, William; Ober, Ciprian (Frontiers in Veterinary Science, 2023)
A 6-year-old female neutered Border Collie presented with an inability to walk. The patient had undergone pelvic limb amputation over a year prior. Orthopedic examination revealed discomfort during hip manipulation, and radiographic examination revealed chronic hip luxation. Total hip replacement was performed using the InnoPlant system, which includes modular screw-in cementless pieces to improve implant stability. Cage rest was for the first four postoperative weeks.Subsequently, assistance was provided while standing until the patient could stand unassisted at ten postoperative weeks. The clinical and radiological outcomes were excellent three months postoperatively. Since it is a new system, there are no data regarding the use of the components of the Innoplant system in dogs with a contralateral amputated pelvic limb. This is the first report describing the use of the Innoplant system for total hip replacement in a dog with a contralateral amputated pelvic limb. Based on the clinical outcomes of this case, the use of an Innoplant prosthesis can be an effective treatment option for dogs with contralateral amputated limbs.